A ten year plan for the economic and social development of the Belgian trust territory of Ruanda-Urundi (New York : Belgian Government Information Center, 1952)
Bibliotheek Camille Huysmans
Dedicator: Goris, Jan-Albert, dedicatee: Huysmans, Camille
Engels
Monografie
Keywords: Ruanda-Urundi.